Long-Term Impact of Direct-Acting Antiviral Agent Therapy in HCV Cirrhosis: Critical Review - Fehily, Sasha R.; Papaluca, Tim; Thompson, Alexander J. (Seminars in Liver Disease, 2019)
More than 70 million people are chronically infected with hepatitis C virus (HCV) worldwide. Chronic hepatitis C is associated with progressive liver fibrosis, which can result in cirrhosis, liver failure, and hepatocellular carcinoma (HCC). HCV-related liver disease has been the most common indication for liver transplantation in the past decade. The development of direct-acting antiviral agents (DAAs) that are simple, well-tolerated, and highly effective means that most people living with hepatitis C can now be cured, leading the World Health Organization to set targets for reduction in deaths due to viral hepatitis by 2030. In this review, the authors will consider the emerging data showing that curative therapy with DAAs can prevent HCV-related morbidity and mortality, with a focus on patients with HCV-related cirrhosis.
Keywords: mortality; decompensation; liver failure; transplant; hepatocellular carcinoma; elimination